2020
DOI: 10.1002/aqc.3374
|View full text |Cite
|
Sign up to set email alerts
|

Residual marine protected areas five years on: Are we still favouring ease of establishment over need for protection?

Abstract: 1.Marine protected areas (MPAs) are today's cornerstone of many marine conservation strategies. Our 2015 study (Devillers et al., 2015) and others have shown, however, that the placement of MPAs is ‘residual’ to commercial uses and biased towards areas of lower economic value or interest. 2.In this paper, we explored the impact of our study on marine science, policy and management practice. 3.We reviewed the papers citing our work and compiled expert opinions on some of the impacts of our study. 4.Results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…We showed that satellite monitoring and perception surveys of various stakeholder groups can support each other in evaluating the performance of MPAs. Thus, it appears that we possess the legal, technical and conceptual tools to protect marine biodiversity via LSMPAs, which work as long as stakeholder involvement is duly considered [105][106][107]. The point is to use these tools.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that satellite monitoring and perception surveys of various stakeholder groups can support each other in evaluating the performance of MPAs. Thus, it appears that we possess the legal, technical and conceptual tools to protect marine biodiversity via LSMPAs, which work as long as stakeholder involvement is duly considered [105][106][107]. The point is to use these tools.…”
Section: Discussionmentioning
confidence: 99%
“…With the impending finalisation of the post-2020 Global Biodiversity Framework, there are calls for a greater spatial protection target of 30% of all land and sea 33 . It is imperative to begin implementing area-based conservation measures in places of high biodiversity value rather than residual areas of limited conservation value 40 . A recent roadmap proposes how the limitations of the Aichi target for site-based conservation can be improved by focusing on outcomes, whereby significant biodiversity sites are “documented, retained, and restored through protected areas and other effective area-based conservation measures” 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Prioritising special features provides some insurance against the declaration of very large offshore MPAs in areas that are of little value to commercial interests (Devillers et al, 2020). In fact, to safeguard against the declaration of large MPAs in areas of little value, this guideline could potentially be adopted firstthe scale of many offshore features and migratory or mobile species ranges makes it highly likely that MPAs designed around Guideline 2 would automatically also be large.…”
Section: Baltar Et Al 2010mentioning
confidence: 99%
“…In data-poor systems, it also provides insurance against missing important, but as yet unknown, features (Rodrigues et al, 2004). 2) Guideline 2 (special areas), because this ensures that largescale MPAs will not be placed in areas that are simply of less commercial interest, but actually include features or species that require protection (Devillers et al, 2020). 3) Guideline 3 (% representation of habitats) where bioregions are not defined or Guideline 4 (% representation of bioregions) where there are defined bioregions at an appropriate scale (Fernandes et al, 2009).…”
Section: Prioritising the Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation